Effects of (+)-Catechin Supplementation on the Some Biochemical Parameters in Sera and Erythrocytes of Ovariectomized Wistar Rats Induced by the Carcinogen Potassium Bromate (KBrO3) - Tuzcu, Mehmet; Irtegun, Sevgi; Yilmaz, Oekkes; Guvenc, Mehmet; Erman, Orhan; Şahin, Kazım (Medwell Online, 2009)
The aim of this research was to examine the effects of (+)-catechin on the levels of Malondialdehyde (MDA), homocysteine, vitamin C, cholesterol, GSH, GSSG and lipophilic vitamins in serum and erythrocytes of old and ovariectomized rats after exposure to the carcinogen potassium bromate. Female Wistar rats (n = 30) were randomly divided into 3 groups. The 1st group was used as a control, the 2nd group was treated with KBrO3 and 3rd group received C + KBrO3. Rats in the KBrO3 and C + KBrO3 groups were injected intraperitoneally with a single dose of KBrO3 (80 mg kg(-1)) in physiological saline. After 2 days, those in the C + KBrO3 group were intraperitoneally injected with catechin (30 mg kg(-1)) 4 times week(-1). Physiological saline was injected into the control group rats. The results indicate that the serum cholesterol level in the KBrO3 group was higher than in the other 2 groups (p<0.01). MDA level was lower in the C + KBrO3 group than the others (p<0.001). The amount of alpha-tocopherol increased in the KBrO3 treated groups (p<0.05, p<0.01). Vitamins C and D-2 levels were higher in the KBrO3 and C + KBrO3 groups than the control group (p<0.001). In erythrocytes, the cholesterol level decreased in the KBrO3 group and the vitamin D-3 level decreased in the C + KBrO3 group (p<0.005). MDA level in the KBrO3 group was higher than the control and C + KBrO3 group (p<0.05). GSH, GSSG and alpha-tocopherol levels were lower in erythrocytes from the KBrO3 and C + KBrO3 groups than the control group (p<0.001). The GSH/GSSG ratio was high in the KBrO3 group; there was no difference between the control and C + KBrO3 groups. In conclusion, it can be said that administration of catechin decreased MDA in the serum and erythrocytes of old and ovariectomized Wistar rats and prevented the decrease of erythrocyte cholesterol.
Keywords: (+)-Catechin; serum; erythrocytes; alpha-tocopherol; Malondialdehyde (MDA); glutathione; ovariectomized Wistar rats; potassium bromate